SINGLE CELL PROTEIN (SCP) REPLACING SOYABEAN MEAL IN BROILER RATIONS - H. Alwash, A.; I. Al-Azzawi, I.; T.0. Al-Tikriti, B.; A.Mekki, A. (The Iraqi Journal of Veterinary Medicine, 1989)
Single cell protein was used to replace 0,7,10,13 and 16% of soyabean meal in diets for broiler chicks up to 51 days of age. In presence of 4% fish meal, ethanol yeast (SCP) could be added at 10% in broiler diet at age 1-24 days and 13% in the diet at age 24-51 days. Chicks given the diets containing 10 and 13% SCP grew significantly (P<0.01) faster than those given 0,7, and 16% SCP. There were significant (P<0.01) differences in the efficiency of feed conversion among different groups.